Mechanical, optical, and physicochemical properties of HPMC-based doxazosin mesylate orodispersible films - Pamela Coradi da Silva; Larissa Aroca Colucci; Larissa Lea da Silva; Celso Molina; Marcelo Dutra Duque; Leticia Norma Carpentieri Rodrigues (Universidade de São Paulo, 2023)
Abstract In this study, orodispersible films formed from hydroxypropyl methylcellulose (HPMC) E6 (2, 2.5, and 3%) and plasticizers ((glycerin (Gly), propylene glycol (PP), or polyethylene glycol (PEG)), containing doxazosin mesylate, were prepared by the solvent casting method and characterized. Design of experiments (DoE) was used as a statistical tool to facilitate the interpretation of the experimental data and allow the identification of optimal levels of factors for maximum formulation performance. Differential scanning calorimetry (DSC) curves and X-ray powder diffraction (XRPD) diffractograms showed doxazosin mesylate amorphization, probably due to complexation with the polymer (HPMC E6), and the glass transition temperature of the polymer was reduced by adding a plasticizer. Fourier transformed infrared (FTIR) spectroscopy results showed that the chemical structure of doxazosin mesylate was preserved when introduced into the polymer matrix, and the plasticizers, glycerin and PEG, affected the polymer matrix with high intensity. The addition of plasticizers increased the elongation at break and adhesiveness (Gly > PEG > PP), confirming the greater plasticizer effect of Gly observed in DSC and FTIR studies. Greater transparency was observed for the orodispersible films prepared using PP. The addition of citric acid as a pH modifier was fundamental for the release of doxazosin mesylate, and the desirability formulation had a release profile similar to that of the reference product.